Rosacea: a wholistic review and update from pathogenesis to diagnosis and therapy. (27th December 2019) - Marson, Justin W.; Baldwin, Hilary E.
Abstract: Rosacea is a chronic inflammatory disorder of the central face with multiple overlapping presentations. Recent advancements are reshaping our understanding of rosacea from both a pathophysiologic perspective and clinical approach to therapy, introducing novel agents that have improved patient outcomes and reduced morbidity. In this article, we aim to outline the advancements in understanding, diagnosing, and managing rosacea and to familiarize physicians with the literature, thereby allowing us to better practice safe and effective medicine.